Altered Vagal Signaling and Its Pathophysiological Roles in Functional Dyspepsia - Li, Hui; Page, Amanda J. (Frontiers in Neuroscience, 2022)
The vagus nerve is crucial in the bidirectional communication between the gut and the brain. It is involved in the modulation of a variety of gut and brain functions. Human studies indicate that the descending vagal signaling from the brain is impaired in functional dyspepsia. Growing evidence indicate that the vagal signaling from gut to brain may also be altered, due to the alteration of a variety of gut signals identified in this disorder. The pathophysiological roles of vagal signaling in functional dyspepsia is still largely unknown, although some studies suggested it may contribute to reduced food intake and gastric motility, increased psychological disorders and pain sensation, nausea and vomiting. Understanding the alteration in vagal signaling and its pathophysiological roles in functional dyspepsia may provide information for new potential therapeutic treatments of this disorder. In this review, we summarize and speculate possible alterations in vagal gut-to-brain and brain-to-gut signaling and the potential pathophysiological roles in functional dyspepsia.